Correlation of Enhanced Strength and Internal Structure for Heat-Treated Submicron Stöber Silica Particles - Romeis, Stefan; Paul, Jonas; Hanisch, Mathias; Marthala, Venkata; Hartmann, Martin; Klupp Taylor, Robin; Schmidt, Jochen; Peukert, Wolfgang (Particle & Particle Systems Characterization, 2014)
The Stöber–Fink–Bohn (SFB) method allows the synthesis of spherical silica particles over a wide size range. Owing to the complex formation mechanism, the internal structure and related mechanical properties are not well understood. Within this account, the internal structure of synthesized SFB particles is changed systematically by heat treatments. Characterization by colloid titration, infrared spectroscopy, and solid-state nuclear magnetic resonance spectroscopy and the assessment of mechanical properties for single particles by in situ micromanipulation shed light on structure–property relations. Over the course of heat treatment, SFB particles become denser and owing to condensation of internal hydroxyl groups, the cross-linking of the silica network is enhanced. The observed chemical and structural changes are reflected by the mechanical properties of the particles: starting from a low Young’s modulus and hardness, clearly below the bulk properties of fused silica, both values are increasing over the course of the thermal treatment. Hardness for fused silica is approached after a treatment at 800 °C and exceeded after a treatment at 1000 °C. Young’s modulus approaches the bulk value. Furthermore, a significant plasticity is found: the sustained deformations are extremely high, and thus silica spheres with enhanced strength have been obtained by the thermal treatment.

In situ deformation and breakage of silica particles inside a SEM - Romeis, Stefan; Paul, Jonas; Herre, Patrick; Hanisch, Mathias; Klupp Taylor, Robin; Schmidt, Jochen; Peukert, Wolfgang (7th World Congress on Particle Technology, WCPT 2014, 2015)
Mechanical properties and particle breakage behavior in the submicron size range are of fundamental importance for many particle related processes and applications. Although many (in situ) studies have been dedicated to materials' size dependent mechanical characterization, particles as free standing structures have been omitted widely. An important, yet open question is the structure property relationship at small scales. Within this account, the application of a custom built manipulator for particle compression inside a scanning electron microscope (SEM) is presented: Stöber-Fink-Bohn (SFB) particles with mean diameters of 500 nm and 1000 nm are subjected to heat treatments and their mechanical properties are directly correlated to the internal structure. The as-synthesized SFB particles exhibit a complex and size dependent internal structure. Mechanical properties undermatching the values of fused silica are found and only plastic cracking at large strains is observed: cracks are formed at the surface and propagate in radial direction towards the particle center. Heat treatment leads to densification. The degree of changes is controlled by temperature and treatment time. Starting from initially low values, Young's modulus and hardness are increasing with treatment temperature. Properties of fused silica are approached or even exceeded after a treatment at 1000°C. A significant level of plasticity and high sustained deformations are still found. Whereas small particle show ductile cracking, the heat treated micron sized particles show a brittle behavior. A brittle to ductile transition in the size range of 500 nm to 1000 nm is thus identified.
Keywords: heat treatment; in situ manipulation; mechanical properties; Stöber silica; Submicron particles

Investigation of interfacial processes leading to anisotropic silver nanostructures on 2D monolayers of silica spheres - Klupp Taylor, Robin; Hanisch, Mathias; Spies, Ines (Investigation of Interfacial Processes Leading to Anisotropic Silver Nanostructures On 2D Monolayers of Silica Spheres, 2013)
One-dimensional nanostructures comprising noble metals are promising materials for a range of electronic, photonic, biomedical and catalysis applications. In particular, their anisotropic morphology opens up possibilities for charge or photonic transport as well as providing a means for the self- or directed-orientation of the building blocks during  fabrication of a functional structure e.g. using electrical fields or fluid forces. In order to enable widespread exploitation of one-dimensional nanostructures, there needs to be more effort to develop and understand simple and scalable routes to achieve them. In this contribution we describe how one-dimensional silver nanoparticle assemblies can be formed at a solid-air interface in the absence of explicitly added reducing and templating agents. We show that in this extremely simple but highly sensitive process, dynamic and strongly anisotropic effects occur during aging of a 2D monolayer of silica nanospheres that had been treated with the ammoniacal silver complex (Ag(NH3)2+). Electron microscopy reveals that 5 – 10 nm silver nanoparticles are arranged in necklace-like assemblies on the silica spheres and up to a certain distance from them on the substrate. We investigate the formation of the nanoparticle necklaces by varying simple parameters of the liquid phase and aging treatments. We also describe attempts to scale-up the process from a few mm2 to cm2, particularly focussing on the formation of the nanostructures on 2D silica nanoparticle monolayers deposited by dip-coating on silicon wafers. We show that together with the simple chemical treatments, dynamic effects at the silica particle monolayer-air interface can lead to a number of interesting morphologies being produced, included the nanoparticle necklaces seen in the smaller scale work. These findings, as well as studies of the interfacial properties of silica help us to narrow down our  mechanistic understanding of the nanostructure formation by the synergistic chemical behavior of the used materials, namely Ag(NH3)2+ and amorphous silica particles. In particular, the presence of dissolved silicates, a result of the high pH of the ammoniacal silver complex appear to be critical. Besides potential uses in transparent electrical conductive coatings, substrates for surface-enhanced Raman spectroscopy (SERS) or for electromagnetic shielding the 1D nanostructures produced by our process  could be particularly interesting for possible novel optical properties of the structures. In the latter case we believe that mesh-coated silica particles formed by their further metallization may display resonances in their magnetization at optical frequencies and thus meets requirements for the formation of, for example, negative index metamaterials.
Keywords: nanostructure; metal; monolayer; surface; particle; noble; assembly

Synthesis of silver nanoparticle necklaces without explicit addition of reducing or templating agents - Hanisch, Mathias; Mackovic, Mirza; Taccardi, Nicola; Spiecker, Erdmann; Klupp Taylor, Robin (Chemical Communications, 2012)
Here we report that silver nanoparticle necklaces can be readily formed by treatment of colloidal silica with ammoniacal silver complex solution followed by washing, deposition and ageing. We investigate the morphology of the produced materials and elucidate the key variables that influence this promising new approach to one-dimensional nanostructuring. © The Royal Society of Chemistry 201
Keywords: templating; agent; nano; particle

Synthesis of silver nanoparticles in melts of amphiphilic polyesters - Vasylyev, Serhiy; Damm, Cornelia; Segets, Doris; Hanisch, Mathias; Taccardi, Nicola; Wasserscheid, Peter; Peukert, Wolfgang (Nanotechnology, 2013)
The current work presents a one-step procedure for the synthesis of amphiphilic silver nanoparticles suitable for production of silver-filled polymeric materials. This solvent free synthesis via reduction of Tollens' reagent as silver precursor in melts of amphiphilic polyesters consisting of hydrophilic poly(ethylene glycol) blocks and hydrophobic alkyl chains allows the production of silver nanoparticles without any by-product formation. This makes them especially interesting for the production of medical devices with antimicrobial properties. In this article the influences of the chain length of the hydrophobic block in the amphiphilic polyesters and the process temperature on the particle size distribution (PSD) and the stability of the particles against agglomeration are discussed. According to the results of spectroscopic and viscosimetric investigations the silver precursor is reduced to elemental silver nanoparticles by a single electron transfer process from the poly(ethylene glycol) chain to the silver ion.